DARK ENERGY AND KEY PHYSICAL PARAMETERS OF CLUSTERS OF GALAXIES - Chernin, A. D.; Bisnovatyi-Kogan, G. S. (Одеські астрономічні публікації, 2012)
We discuss the physics of clusters of galaxies embedded in the cosmic dark energy background and show that 1) the halo cut-off radius of a cluster like the Virgo cluster is practically, if not exactly, equal to the zero-gravity radius at which the dark matter gravity is balanced by the dark energy antigravity; 2) the halo averaged density is equal to two densities of dark energy; 3) the halo edge (cut-off) density is the dark energy density with a numerical factor of the unity order slightly depending on the halo profile.